Stabilization of subgrade by using fly ash related to road pavement thickness design at Jalan Jaya Gading - Mohd Ashraf, Mohd Hussin (2010)
This project aims to study the effectiveness of adding fly ash by percentage to the subgrade with increasing the California Bearing Ratio (CBR) value. The fly ash will be added to the plain soil (subgrade) by using 4% and 8% fly ash and tested by following ASSHTO as guidance steps. California Bearing Ratio (CBR) is a commonly used directly as to assess the stiffness modulus and shear strength of subgrade in pavement design work. If the CBR value is increasing by adding the fly ash to the soils it's shown its effectiveness in increasing soil strength and vice versa Overall, when California Bearing Ratio (CBR) value increases, the thickness of pavement design can be reduced and subsequently the road construction of the affected road section will be more economically.